Arbuscular Mycorrhizal and endophytic (DSE) association in the dominant grasses of Melghat forest (Phase -I), India - Deotare, P W; Khodke, S P; Maggirwar, R C; Kharwade, S K (Plantae Scientia, 2019)
Investigations on arbuscular mycorrhizal Fungi (AMF) and dark septate endophytic (DSE) association in some of the dominant grasses from Melghat forest (phase I) of Satpura terrain India, was carried out to examine their existence and symbiotic relationships with the host plants. This forest area was not surveyed earlier by anybody to evaluate the AMF status diversity hence it was decided to survey the buffer and core area. Rhizosphere soil of each sampled grass was analyzed for the AM fungal structures in the roots to study percent root colonization by AMF and AMF spore density in rhizospheric soils of respective samples. The composite soil sample was prepared for each site and used for physicochemical analysis by standard methods. In the first phase of project, forty-eight dominant grass species from twenty-one different sites were collected along with roots and rhizospheric soil to find out AMF and DSE status of grasses. Both type of fungal associations was found in almost all the grass species collected during studies. All of them were found colonized by AMF hyphae along with moderate to poor development of mycorrhizal structures in roots. DSE colonization was also found in maximum forty-three grasses. Physico- chemical characterization of all the soil samples were performed to find out its correlation with AM percent colonization and spore count. Mean AMF percent colonization were in between 1.33 to 52.85 and DSE in with 0.00 to 18.97. Viable AM spore count were in between 0 to 98 per 100g of soil. Altogether four AMF genera with its thirty-nine-different species were isolated and identified. A data base of indigenous AM species richness for Melghat forest has been generated to plan and design the future management practices for grasses establishment and development especially in burnt and over grazed areas.